Comparing the emotional well - being, marital intimacy and quality of life of mothers of children with attention deficit / hyperactivity disorder and mothers of normal children - Ali Sheykholeslami; Sara Taghizadeh Hir; Pezhman Honarmand Ghojabeyglou; Alireza Moradiyan (مجله علوم روانشناختی, 2020)
Background: Studies on quality of life, mental health and anxiety and depression in parents of children with attention deficit / hyperactivity disorder have been conducted. But the main issue is that research comparing emotional well-being, marital intimacy, and quality of life of mothers of children with ADHD with mothers of normal children has been neglected. Aims: The aim of this study was to compare the emotional well-being, marital intimacy and quality of life of mothers of children with ADHD with mothers of normal children. Method: This study was a descriptive causal-comparative study. The statistical population of the study consisted of all mothers of children with attention deficit / hyperactivity disorder and mothers of normal children in Ardebil in 2015-2016. Mothers with children with attention deficit / hyperactivity disorder and 60 mothers with normal children were selected as the sample. Data were analyzed using the revised Conner Parent-Short Form Rating Scale (Conners, 1999), Clinical Interview, Emotional Well-being Components' of Keyes and Magyaromo Subjective Well-being Questionnaire (2003), Bougarose's Marital Intimacy Questionnaire (2001), and the Organization Quality of Life Questionnaire. Global Health-Short Form (1998) was collected. Multivariate analysis of variance was used to analyze the data. Results: The results showed that emotional well-being, marital intimacy and quality of life of mothers of children with attention deficit / hyperactivity disorder were significantly lower than normal mothers (P<0/01). Conclusions: Mothers of children with attention deficit / hyperactivity disorder have lower levels of emotional well-being, marital intimacy, and quality of life than mothers of normal children